Ultrasound guided anterior approach to intra‐articular injection of the knee. Issue 3 (23rd December 2021) - Adamiak, Paul; Inkpen, Peter; Bardi, Mohammad
Abstract: In this clinical practice article, we describe a novel, anterior, approach for therapeutic intra‐articular injection of the knee under ultrasound guidance. The benefits of this approach are improved accuracy in knees that do not have an effusion, simplified sonoanatomy for learners, and easy localization in patients with enlarged body habitus or altered anatomy. This article describes the positioning, sonographic anatomy, risks, and technical considerations for this anterior approach. Abstract : The graphical abstract image depicts the in‐plane view of the ultrasound guided, anterior approach to intra‐articular injection of the knee. The benefits of the approach presented here include simplified sonographic anatomy, easy localization of the injection target in patients with altered anatomy, and improved injection accuracy in knees lacking an effusion.